Hidden photon dark matter in the light of XENON1T and stellar cooling - Alonso Álvarez, Gonzalo; Ertas, Fatih; Jaeckel, Joerg; Kahlhoefer, Felix; Thormaehlen, Lennert J. (Journal of cosmology and astroparticle physics, 2020)
The low-energy electronic recoil spectrum in XENON1T provides an intriguing hint for potential new physics. At the same time, observations of horizontal branch stars favor the existence of a small amount of extra cooling compared to the one expected from the Standard Model particle content. In this note, we argue that a hidden photon with a mass of ∼ 2.5 keV and a kinetic mixing of ∼ 10−15 allows for a good fit to both of these excesses. In this scenario, the signal detected in XENON1T is due to the absorption of hidden photon dark matter particles, whereas the anomalous cooling of horizontal branch stars arises from resonant production of hidden photons in the stellar interior.
Gesehen am 11.12.2020